2019
DOI: 10.1007/s00787-019-01313-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic comorbidity in children and adolescents with psychiatric disorders

Abstract: In the adult population, psychiatric disorders are associated with somatic illness. Explanatory life style factors have been found, but also a failure to recognize somatic illness in this group. Another factor is side effects from long-term use of antipsychotic drugs. Given the psychiatric-somatic comorbidity in the adult population, it is of interest to investigate whether an association exists already during childhood. The aim of the present study was to investigate the frequency of somatic illness in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
3
27
0
1
Order By: Relevance
“…A systematic review demonstrated a strong positive association between chronic somatic disorders in adolescence and anxiety and depressive disorders [16]. A recent population-based Swedish study reported a high risk for concurrent somatic disorders in children with psychiatric disorders, across all ages and across many types of conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review demonstrated a strong positive association between chronic somatic disorders in adolescence and anxiety and depressive disorders [16]. A recent population-based Swedish study reported a high risk for concurrent somatic disorders in children with psychiatric disorders, across all ages and across many types of conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic symptoms can simply represent the bodily manifestation of distress that accompanies a wide range of mental health issues (e.g., depression and anxiety) [ 64 ]. However, two well-designed population studies found a significant concurrence of somatic symptoms and psychosis in pre-adolescent and adolescent research participants [ 16 , 65 ]. The relationship between somatic symptoms and psychotic-like experiences appeared to be independent of anxiety or other forms of psychopathology, possibly representing anomalous interpretations of bodily experiences [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DTD domain of affective/somatic dysregulation (Criterion B) includes four symptoms that are based on research showing that maladaptive emotion processing and emotion dysregulation are a link between childhood adversity and subsequent psychopathology extending into adolescence and adulthood (Aldao et al, 2016;Beauchaine & Cicchetti, 2019;Conway et al, 2018;Heleniak et al, 2016b;McLaughlin et al, 2020;Schaefer et al, 2021;Weissman et al, 2019). Somatic dysregulation (i.e., impairment in or pain related to basic bodily functions) was included in this domain based on to evidence that children may express emotional distress indirectly through somatic complaints and somatoform symptoms (Agnafors et al, 2019;Flaherty , 2013;Ford et al, 2013b;Vernberg et al, 2011). In addition, adults (Eslami et al, 2019;Littleton, 2015;Paras et al, 2009) and adolescents (Bonvanie et al, 2015;Espejo-Siles et al, 2020;Nixon et al, 2011;Rey et al, 2020) with a history of childhood sexual abuse or peer victimization are at risk for stress-related somatic complaints and bodily problems (i.e., functional gastrointestinal disorders, chronic nonspecific and pelvic pain, psychogenic seizures).…”
Section: Criteria For Developmental Trauma Disordermentioning
confidence: 99%